The Bark Extraction of Salix Aegyptiaca L Antibacterial Activity - ABDALRAHMAN, MAAROOF RASUL; SOFI, SHNO ABDALQADIR (The journal of contemporary issues in business and government, 2021)
The use of plants as a source of medicine has been a part of life in the world since ancient times. Many modern pharmaceuticals are based on plant-based drugs, and they are used to treat a range of illnesses in today’s society. The aim of this research was to identify alternative compounds that could be used in the production of antimicrobial compounds. It is expected that a compound that can be used as a raw material for antimicrobial agents will be discovered. Salix alba has been used as medicine for a long time. We conclude that Salix aegyptiaca bark extract can be used as a safe and effective drug for Candidiasis based on the results.